Transformative Leadership to Enhance the Quality of Madrasa in the Covid-19 Outbreak: Learning Organization Perspective - Susanto Susanto (Ta'dib: Jurnal Pendidikan Islam, 2022)
This study aims to identify the implementation of transformative leadership in a madrasa in East Java. It was based on Peter Senge's learning organization theory. Moreover, this study employed quantitative descriptive research using the online survey method. It involved the leaders and the teachers of madrasa in East Java. The data was taken from February to April 2021. The respondents were 90 leaders and the teachers of all levels of madrasa – MI, MTs, and MA. It used random sampling. The researcher gathered the data from the questionnaires through Google Forms. Then, the data were analyzed descriptively. Based on Peter Senge's five-learning organization, transformative leadership implementation was found in madrasa during the Covid-19 outbreak. First, the systems thinking of teachers and education staff in madrasa during the outbreak had two indicators. The transformation of the madrasa service system based on some considerations is 75%. The curriculum adjustment also is 79%. Second, the implementation of personal mastery was through two indicators – learning new things and facing the challenges is 78%, and relevant learning method innovation is 81%. Third, the mental model is based on two indicators. They are the thinking skills quality improvement for better competence is 78% and improving the school system focused on the service quality is 83%. Fourth is the implementation of a shared vision which is based on two indicators. 79% of schools' communities comprehend the school vision. It also shows that the task completion based on the school vision is 86%. Fifth, team learning is based on two indicators. The peer group sharing habit is 90%, and fostering a dialogue culture with the leaders to improve school quality is 87%. In conclusion, this study shows that the implementation of transformative leadership enhances the madrasas’ quality amidst the covid-19 based on a learning organization perspective.